THE BASIC MEANINGS OF ROOT VERBS AND AUGMENTED VERBS IN SURAT YASIN - Alif Cahya Setiyadi; Neda Azzah Saniyyah; Aufa Alfian Musthofa; Sania Karimah Liputo (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
The main objectives of this research are (1) to understand the basic meanings of verb augmentation in Surat Yasin, and (2) to identify the benefits of additional letters in verbs within Surat Yasin. To achieve these objectives, the researcher employed a literature review method. Data sources included the verses from Surat Yasin as recorded in the Noble Qur’an published by the Department of Religion of the Republic of Indonesia in 2009. Secondary sources consisted of books related to morphology, verb studies, and research methodology. The document analysis method was used. The results indicate that the basic meanings of verb augmentation in Surat Yasin involve verbs with letter additions, including verbs with two or three added letters. The benefits of single-letter augmentation include emphasis, transitivity, process, and exaggeration. The benefits of two-letter augmentation involve further emphasis and increased transitivity. The benefit of three-letter augmentation is transformation. Based on these findings, it is recommended that future researchers investigate the grammatical meanings of verbs in Surat Yasin or explore the basic meanings of augmented verbs in other surahs of the Qur’an.